A Critical Analysis of the Trends in Low Measles-Containing-Caccine First- and Second Dose (MCV1 & 2) Immunization Coverage among 1-Year-Olds in Venezuela, 2009-2024 - Rodriguez-Morales, Alfonso J.; CardonaOspina, Jaime A.; Avila-Tangarife, Maria Alejandra; Salazar Ledesma, Carmen Rosa; Cedeño, Maria Paula; Olarte Duran, Mely Alexandra; Soto Ramírez, Deicy Mariana; Acevedo, Domenica; Malavet, Thomas; Marmolejo, Valeria; Moghnieh, Rima; Husni, Rola; et al. (REVISTA CIENTÍFICA SALUD UNINORTE, 2025)
Introduction: Recently, measles has reemerged as a significant public health concern globally, affecting countries in Latin America, particularly children in areas facing low vaccination coverage and political or socioeconomic instability. Despite being a vaccine-preventable disease with elimination goals established by the World Health Organization (WHO), measles immunization rates in several Latin American countries remain below the recommended thresholds, increasing the risk of outbreaks and regional transmission amid epidemics in North America. The objectives of this study were to assess measles vaccine trends and indicators in Venezuela. Methods: Using PAHO, the WHO/UNICEF Joint Reporting Form on Immunization, and the WHO/UNICEF Estimates of National Immunization Coverage (WUENIC) data from the Venezuelan Ministry of Health, a trend analysis of immunization coverage of under-1-year-olds against measles in Venezuela, 2009-2024 (Measles-containing-vaccine first- and second-dose, MCV1/2, immunization coverage among 1-year-olds), with an ecological approach, was done. Additionally, cases of measles infections were considered and analyzed. Variations in rates and other analyses were made. Results: Immunization coverage of under-1-year-olds varied from 87% in 2009 (MCV1) to a maximum of 96% in 2017. Since 2017, a significant reduction trend (r²=0.600, p=0.0409, linear regression) up to 2023 has been observed, reaching 52% in 2022, slightly recovering to 68% in 2023, and 71% in 2024. Specifically, from 2011 to 2019, low MCV1 vaccine coverage was significantly associated with an increase in measles cases (6,943 cases during the period) (r²=0.9600, p<0.0001, non-linear regression). No significant associations were observed between MCV2 and measles cases (p?0.05). Conclusions: Measles immunization coverage in Venezuela has declined significantly since 2017, contributing to an increase in measles cases, particularly in areas where first-dose coverage (MCV1) fell below the recommended levels. Therefore, strengthening routine immunization programs and addressing coverage gaps are urgently needed to prevent future outbreaks and progress toward measles elimination goals in the country and the region.